Analysis of effusion cooling under realistic swirl reacting flow in gas turbine combustor. (5th November 2022) - Ji, Yongbin; Ge, Bing; Zang, Shusheng
Highlights: Orthogonal effusion hole scheme offers better cooling than the forward one at large coolant flowrate thanks to the more intense convective heat transfer inside holes and lower driving temperature on the hot side. The backward injections pose potential to resist the main swirl flow impinging impact at realistic reacting conditions and it can be applied for the optimization design of combustor liner cooling. The built-up layer of film developed from backward jets gets impeded but pushes the main flow back to upstream and away from cooled plate. Abstract: Cooling performance is experimentally and numerically investigated in an effusion-cooled, swirl-stabilized three-sector gas turbine combustor at realistic reacting flows. The temperature distribution on the perforated wall is measured by the infrared thermography and the overall cooling effectiveness is evaluated at the conjugate heat transfer condition. The effusion holes are inclined at 30°, 90° and 150° to explore the effect of cooling injection direction on the effusion cooling effectiveness and flame-cooling interaction. The pressure drop across the cooling plate and the equivalence ratio are varied to assess their influences on the effusion cooling behavior. Weak interaction between the main flow and cooling jets is observed for the forward cooling hole scheme, but the impingement region caused by the expanding main flow brushing on the liner wall suffers from the insufficient cooling protection. The orthogonal holes present relatively higher overall cooling effectiveness than the forward one because of the larger amount of air removing the heat loaded on the liner wall via convection flow inside the holes. In addition, the vertical cooling injections lift the main flow upwards and thus decrease the driven heat transfer temperature. It is most noteworthy that the backward injections present potentials to resist the impingement impact, its overall cooling effectiveness demonstrates to be the highest especially when the coolant amount is adequate enough.